Obesity and metabolic syndrome as risk factors for the development of non-alcoholic fatty liver disease as diagnosed by ultrasound - Petrović, Gordana; Bjelaković, Goran; Benedeto Stojanov, Daniela; Nagorni, Aleksandar; Brzački, Vesna; Marković-Živković, Bojana (Vojnosanitetski pregled, 2017)
Background/Aim. Non-alcoholic fatty liver disease (NAFLD) is a chronic liver disease of a broad histological spectrum, characterized by the accumulation of triglycerides in more than 5% of hepatocytes in the absence of consuming alcohol in quantities harmful to the liver. The aim of our study was to determine the importance of anthropometric and laboratory parameters as well as metabolic syndrome for the diagnosis of NAFLD and to estimate their influence on the degree of liver steatosis as evaluated by ultrasound. Methods. The study included 86 participants, 55 of whom had fatty liver diagnosed by ultrasound and they comprised the study group. The control group consisted of 31 subjects with no liver diseases. During the course of hospitalization at the Clinic of Gastroenterology and Hepatology, Clinical Centre Niš, the patients had their anamnesis taken, and anthropometric measurements as well as biochemical blood analyses and abdominal ultrasound were performed. Results. The patients with NAFLD had statistically higher values of body mass index (BMI), waist circumference (WC), systolic (SBP) and diastolic blood pressure (DBP), levels of alanine and aspartate aminotransferase (ALT, AST), gamma-glutamyl transpeptidase (GGT) (p < 0.001), low-density lipoprotein cholesterol (LDL), total bilirubin (TBIL) (p < 0.05), total cholesterol (p < 0.01), triglycerides (TGL), urates, C-reactive protein (CRP), ferritin, fibrinogenes, fasting blood glucose (FBG), insulin and Homeostasis Model Assessment (HOMA-IR) (p < 0.001) compared to the control group, whereas the levels of high-density lipoprotein cholesterol (HDL) were higher in the control than in the study group (p < 0.05). In the NAFLD group, there were statistically significantly more patients with hypertension (72.73% vs 12.90%, p < 0.001) and type 2 diabetes mellitus (DM) (47.27%). Metabolic syndrome was established in 48 (87.27%) patients of the study group. The equal number of patients, ie 16 (29.09%), had 3, 4 and 5 components of MS. In the NAFLD group there were 17 (30.91%) overweight (BMI from 25 kg/m2 to 29.9 kg/m2) and 38 (69.09%) obese patients (BMI ≥ 30.0 kg/m2). The largest number of patients in the obesity group, 22 (40.00%) of them, had the first degree obesity (BMI from 30 kg/m2 to 34.99 kg/m2). The largest number of the NAFLD group patients, 23 (41.82%), had an ultrasound finding of grade 3 fatty liver, 20 (36.36%) patients had grade 2 and 12 (21.82%) grade 1 fatty liver. Kruskal-Wallis test and ANOVA analysis showed statistically significant differences between groups with different US grade for insulin, LDL-cholesterol, WC, BMI (p < 0.05), as well as HOMA-IR and body weight (BW) (p < 0.01). Metabolic syndrome was statistically more present in patients with US finding grades 2 and 3 (p < 0.01) in relation to US finding grade 1, as well as obesity, hypertension and DM type 2 (p < 0.05). Conclusion. The results of our study confirm that a high percentage of patients with high risk factors (DM, MS, dyslipidemia, hypertension) have NAFLD.